"You Don't Have to Like Me, But You Have to Respect Me": The Impacts of Assertiveness, Cooperativeness, and Group Satisfaction in Collaborative Assignments. (June 2016) - Lambertz-Berndt, Megan M.; Blight, Michael G.
This study investigates cooperativeness, assertiveness, group satisfaction, leader grade, and leadership negotiation in a collaborative assignment conducted in a small group. Researchers manipulated the assignment of team members who reported on measures of group satisfaction and original scales of assertiveness and cooperativeness. Respondents also responded to open-ended questions regarding active leadership, leadership traits, and leadership negotiation, which resulted in the emergence of multiple themes. Assertiveness, cooperativeness, and group satisfaction were found to predict the grade given to the leader.